2012
DOI: 10.1103/physrevlett.108.218105
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Dewetting: Opening of Macroapertures in Endothelial Cells

Abstract: Pathogenic bacteria can cross from blood vessels to host tissues by opening transendothelial cell macroapertures (TEMs). To induce TEM opening, bacteria intoxicate endothelial cells with proteins that disrupt the contractile cytoskeletal network. Cell membrane tension is no longer resisted by contractile fibers, leading to the opening of TEMs. Here we model the opening of TEMs as a new form of dewetting. While liquid dewetting is irreversible, we show that cellular dewetting is transient. Our model predicts th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(77 citation statements)
references
References 18 publications
1
76
0
Order By: Relevance
“…Two recent studies have revealed that TEM tunnel opening can be described as a cellular form of dewetting, that is, the physical processes governing TEM are analogous to those governing the opening of dry patches in liquid films (Box 1 and see Maddugoda et al, 2011;Gonzalez-Rodriguez et al, 2012 for biological and physical details). Liquid dewetting is a very common phenomenon that occurs for instance when water is forced to spread on a hydrophobic substrate or when oil is heated on a non-adhering pan.…”
Section: General Aspects Of Liquid and Cellular Forms Of Dewettingmentioning
confidence: 99%
See 3 more Smart Citations
“…Two recent studies have revealed that TEM tunnel opening can be described as a cellular form of dewetting, that is, the physical processes governing TEM are analogous to those governing the opening of dry patches in liquid films (Box 1 and see Maddugoda et al, 2011;Gonzalez-Rodriguez et al, 2012 for biological and physical details). Liquid dewetting is a very common phenomenon that occurs for instance when water is forced to spread on a hydrophobic substrate or when oil is heated on a non-adhering pan.…”
Section: General Aspects Of Liquid and Cellular Forms Of Dewettingmentioning
confidence: 99%
“…Excessive contraction or disruption of the actin cytoskeleton cortex leads to the local detachment of the membrane associated with induction of membrane blebs (Sheetz et al, 2006;Ridley, 2011;Spangler et al, 2011;Salbreux et al, 2012). In contrast, a reduction of actomyosin cable contractility produces large tunnels across thin endothelial cells, referred to as transendothelial cell macroaperture tunnels (TEMs) (Boyer et al, 2006;Maddugoda et al, 2011;Gonzalez-Rodriguez et al, 2012). Internal cellular regulation usually inhibits the spontaneous formation of such TEMs, but some bacterial toxins or leucocytes have the capability to induce TEMs to cross the endothelial barrier .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Many periodic systems can relax towards equilibrium when a large enough disturbance appears, such as supercooled liquids [2], dewetting cells [3], snow avalanches [4] and nucleating bubbles in liquids [5]. Of particular note are instabilities driven by a competition between weight and magnetic forces created by permanent magnets.…”
Section: Introductionmentioning
confidence: 99%